PEMBERDAYAAN PEREMPUAN MELALUI BISNIS KREATIF WEDDING ORGANIZER UNTUK MEMBANGUN KEMANDIRIAN EKONOMI PKK DESA CIWARUGA KABUPATEN BANDUNG BARAT - Deti Rostini; Okke Rosmaladewi; Siti Nur; Ahmad Saeful Ridwan (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The development of community-based creative enterprises has become an effective strategy to enhance rural economic independence. However, the skills of the women’s community group (PKK) in Ciwaruga Village, West Bandung Regency—such as sewing, make-up artistry, cooking, and decoration—have not been fully utilized in an organized business. This issue highlights the need for an innovative creative business in the form of a Wedding Organizer (WO) that integrates local skills with Sundanese cultural wisdom. The method applied in this program was a participatory empowerment approach. The stages included identifying human resource potentials and local wisdom, mapping infrastructure and collaboration opportunities with local MSMEs, conducting training on WO management and digital marketing, and designing a collaborative business model. The results indicate that PKK members are able to contribute significantly to WO services such as bridal make-up, decoration, catering, and the production of local souvenirs. Furthermore, social networking and the use of digital media proved effective in enhancing promotion, while synergy with local MSMEs strengthened business sustainability and created more comprehensive wedding service packages with cultural value. In conclusion, the development of a women-empowered WO in Ciwaruga Village not only generates new economic opportunities but also reinforces local cultural identity and supports family independence. This model has the potential to be replicated in other villages as a strategy for community-based creative economic development.